PERAN NOTARIS PASAR MODAL DALAM PROSES PELAKSANAAN GO PRIVATE SEBUAH PERSEROAN TERBATAS - WILLIANA HALIM (PREMISE LAW JURNAL, 2016)
Go public is one of the choices to the companies that will need additional capital to run and develop their business activities. However, when the benefit of going public is no longer effective to the companies, they will prefer to go private, which is an action of open limited liability companies to switch their status by eliminating their stock notes in the stock exchange. As one of the capital market supporting professional, a notary also takes part in either the implementation of go public or go private. The capital market notary should possess the knowledge of capital market and has registered himself/herself to the Financial Service Authority. Notary plays a role in the articles of association of each capital market person and the making of important deeds such as agreements of investment fund, emission guaranty, and trustee. Notary is also responsible for the deeds, either civilly, criminally, or administratively. Keywords: Go Private, Notary Operating in Capital Market, Limited Liability Companies